The culturable microbiological landscape of guarana-based products and wastes: insights from the Amazon state (Brazil) production chain - Dionisio Pedro Amorim-Neto; Clara Mariana Gonçalves Lima; Simone de Nazaré Melo Ramos; Raimunda Susielen Ribeiro Araújo; Ana Luisa Perini Leme Giordano; Angélica Zaninelli Schreiber; Anderson S. Sant’Ana; Priscilla Efraim (Applied Food Research, 2025)
Guarana, a fruit native to South America, is a key ingredient in various products, including beverages and supplements, due to the high caffeine content, which gives the drinks stimulating properties. While the chemical properties of guarana seeds are well-studied, their microbiological profile remains largely unknown. For this reason, this study investigates the microbiological characteristics of guarana-based products and by-products, focusing on quantifying viable spoilage microorganisms, pathogens, and opportunists throughout the guarana production chain. The study also assessed water activity and pH across different guarana products, noting that most products had low water activity (0.501–0.918) and acidic pH levels (4.97–6.65), similar to other processed fruits such as coffee and cocoa. Despite these conditions, microbial populations, including spore-forming bacteria such as Bacillus cereus and potential pathogens like Cronobacter sp. and Enterobacter cloacae, were detected. These microorganisms pose significant food safety concerns, as some can survive harsh processing conditions and cause severe health issues. However, pathogens like Salmonella and Listeria monocytogenes were not detected. Notably, guarana powder, often consumed directly, exhibited high microbial counts, highlighting the need for improved hygiene and good manufacturing practices throughout the guarana production chain to ensure consumer safety.